Estudo sobre clima organizacional e desempenho financeiro em algumas empresas brasileiras de capital aberto - Lopes, Thais Rodrigues Alves Valle [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Despite the fact that it is a recent study, the relationship between organizational climate and financial performance has been discussed a lot. The efficient management of organizational climate can be a strategic tool for business success. Employees that are satisfied, motivated and aligned with company's strategy produce more and, consequently, improve the financial results of the company they work. The aim of this work is qualitatively verify the possible relationship between the results of organizational climate surveys in three Brazilian public companies and financial indicators between 2010 and 2015. There was convergence of the results of organizational climate surveys and financial indicators in two of the three companies. This work has contributed to strengthening the Herzberg and Maslow's theories of motivation and also to enlarge the importance of managing the organizational climate and finally, to encourage companies to be more concerned with the satisfaction of its employees. It is recommended more studies that are empirical should be conducted to assess greater consistency of results

Apesar de ser um estudo novo, a relação entre clima organizacional e desempenho financeiro tem sido muito estudada. O gerenciamento eficiente do clima organizacional pode ser uma ferramenta estratégica para o sucesso dos negócios. Funcionários satisfeitos, motivados e alinhados a estratégia da empresa produzem mais e, em consequência, melhoram o resultado financeiro da empresa que trabalham. O objetivo é verificar qualitativamente as possíveis relações entre os resultados de pesquisas de clima organizacional de três empresas brasileiras de capital aberto e indicadores financeiros entre 2010 e 2015. Verificou-se convergência dos resultados de clima organizacional e indicadores financeiros em duas das três empresas. Este trabalho contribuiu para reforçar as teorias de motivação de Herzberg e Maslow e também para ampliar a importância da gestão do clima organizacional e por fim, para incentivar as empresas a se preocuparem mais com a satisfação dos seus funcionários. Recomenda-se que mais estudos empíricos devem ser conduzidos para se aferir uma maior consistência dos resultados
Keywords: Clima organizacional; Motivação no trabalho; Indicadores econômicos; Economic indicators